Bio-engineering a prevascularized human tri-layered skin substitute containing a hypodermis. (15th October 2021) - Zimoch, Jakub; Zielinska, Dominika; Michalak-Micka, Katarzyna; Rütsche, Dominic; Böni, Roland; Biedermann, Thomas; Klar, Agnes S.
Abstract: Severe injuries to skin including hypodermis require full-thickness skin replacement. Here, we bioengineered a tri-layered human skin substitute (TLSS) containing the epidermis, dermis, and hypodermis. The hypodermal layer was generated by differentiation of human adipose stem cells (ASC) in a collagen type I hydrogel and combined with a prevascularized dermis consisting of human dermal microvascular endothelial cells and fibroblasts, which arranged into a dense vascular network. Subsequently, keratinocytes were seeded on top to generate the epidermal layer of the TLSS. The differentiation of ASC into adipocytes was confirmed in vitro on the mRNA level by the presence of adiponectin, as well as by the expression of perilipin and FABP-4 proteins. Moreover, functional characteristics of the hypodermis in vitro and in vivo were evaluated by Oil Red O, BODIPY, and AdipoRed stainings visualizing intracellular lipid droplets. Further, we demonstrated that both undifferentiated ASC and mature adipocytes present in the hypodermis influenced the keratinocyte maturation and homeostasis in the skin substitutes after transplantation. In particular, an enhanced secretion of TGF-β1 by these cells affected the epidermal morphogenesis as assessed by the expression of key proteins involved in the epidermal differentiation including cytokeratin 1, 10, 19 and cornified envelope formation such as involucrin. Here, we propose a novel functional hypodermal-dermo-epidermal tri-layered skin substitute containing blood capillaries that efficiently promote regeneration of skin defects. Statement of significance: The main objective of this study was to develop and assess the usefulness of a tri-layered human prevascularized skin substitute (TLSS) containing an epidermis, dermis, and hypodermis. The bioengineered hypodermis was generated from human adipose mesenchymal stem cells (ASC) and combined with a prevascularized dermis and epidermis. The TLSS represents an exceptional model for studying the role of cell-cell and cell-matrix interactions in vitro and in vivo . In particular, we observed that enhanced secretion of TGF-β1 in the hypodermis exerted a profound impact on fibroblast and keratinocyte differentiation, as well as epidermal barrier formation and homeostasis. Therefore, improved understanding of the cell-cell interactions in such a physiological skin model is essential to gain insights into different aspects of wound healing. Graphical abstract: Image, graphical abstract